Rapid regression of neurological symptoms in patients with metastasised ALK+ lung cancer who are treated with lorlatinib: a report of two cases. Issue 7 (24th July 2019) - Gafer, Huda; de Waard, Quincy; Compter, Annette; van den Heuvel, Michel
Abstract : Oral anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKI) have shown significant benefit in the management of ALK-rearranged non-small cell lung cancer (NSCLC). However, almost all patients will experience disease progression after front-line ALK-TKIs such as crizotinib. Treatment with third generation ALK-TKI lorlatinib can have a significant clinical impact following disease progression, even in patients with a very poor performance status. Here, we review two clinical cases with metastatic ALK-rearranged NSCLC who had pulmonary disease control with first-generation ALK inhibitor. However, disease progressed rapidly in the central nervous system with severe neurological symptoms. Treatment with lorlatinib, a third-generation ALK-TKI, led to a rapid radiological and clinical cerebral response in both patients. Lorlatinib can overcome ALK resistance to crizotinib, and the presented cases suggest a potential role for lorlatinib in patients with rapidly progressive cerebral and leptomeningeal metastases.